When God Made the Tree - Kroll, Virginia; Nang ChanYeema (Hong Kong Dawn Publication, 1999)
Presidents thirteen different tree species around the world and describes how they carry out God's plan by supporting people and animals in a harmonious relationship.
Keywords: Juvenile Nonfiction